Plan de negocios: restaurante vegetariano (2020)
The year 2020 was a year with totally unexpected events for the world population. The pandemic generated by the COVID-19 virus notably affected the economy of all countries, notably impacting the restaurant sector. Due to the implications of this virus, a large number of restaurants had to close or declare bankruptcy; the rest had the need to reinvent themselves to continue offering their services to the general public. This business plan aims to analyze the viability of creating a vegetarian restaurant that complies with the necessary regulations, especially taking into account those related to new biosecurity measures. This idea arose because my mother's restaurant was one of those affected by the global pandemic, the costs and expenses were very high when the general quarantine was established in Colombia. This led to an economic analysis to determine if it was feasible to maintain the business through domiciles, something that ended with the closure of the business after 15 years in the sector. Prior to the development of this business plan, a market research and analysis was carried out to determine the viability of the business, which allowed us to realize that the vegetarian restaurant market is in its growth stage, so it would be very interesting to raise a vegetarian restaurant in the city of Bogotá. This will have a differentiating factor such as value for money, as well as a concept of environmental sustainability that will attract the attention of more customers. In the following document, a business model was made where all the necessary aspects are analyzed and developed to evaluate the viability of the restaurant and, in the case of obtaining good results, study the possibility of implementing it.